Capacity assessment to support food systems transformation towards sustainable healthy diets in Bangladesh: Exploring the capabilities of the SHiFT strategic partners - Namugumya, Brenda S.; Abedin, Jainal; Herens, Marion (International Food Policy Research Institute, 2024)
Strengthening the multidisciplinary capabilities necessary to accelerate food systems transformation has garnered increased interest over the past decade. A capabilities assessment was done with the Strategic Partners of the CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation in Bangladesh to understand their abilities to facilitate transformative changes towards sustainable healthy diets. Both Strategic Partners, the Food Planning and Monitoring Unit (FPMU) and the Bangladesh National Nutrition Council (BNNC), have long histories and well-established structures for collaboration and coordination with diverse stakeholders to realize the nutrition-focused (BNNC) and the food-related (FPMU) ambitions of the Government of Bangladesh. They are engaged in food and/or nutrition policy development, governance of the sectors, and monitoring progress at both national and sub-national levels. Using a capability assessment tool tailored to capturing food systems transformation capabilities at organizational level, the capabilities to deliver results and adapt and self-renew were the highest scored for FPMU. BNNC scored more on the capabilities to achieve coherence and to relate to support food systems transformation higher.